Associations of Polyunsaturated Fatty Acid Intake with Bone Mineral Density in Postmenopausal Women - Margaret Harris; Vanessa Farrell; Linda Houtkooper; Scott Going; Timothy Lohman (Journal of Osteoporosis)
A secondary analysis of cross-sectional data was analyzed from 6 cohorts (Fall 1995–Fall 1997) of postmenopausal women (n=266; 56.6±4.7 years) participating in the Bone Estrogen Strength Training (BEST) study (a 12-month, block-randomized, clinical trial). Bone mineral density (BMD) was measured at femur neck and trochanter, lumbar spine (L2–L4), and total body BMD using dual-energy X-ray absorptiometry (DXA). Mean dietary polyunsaturated fatty acids (PUFAs) intakes were assessed using 8 days of diet records. Multiple linear regression was used to examine associations between dietary PUFAs and BMD. Covariates included in the models were total energy intake, body weight at year 1, years after menopause, exercise, use of hormone therapy (HT), total calcium, and total iron intakes. In the total sample, lumbar spine and total body BMD had significant negative associations with dietary PUFA intake at P<0.05. In the non-HT group, no significant associations between dietary PUFA intake and BMD were seen. In the HT group, significant inverse associations with dietary PUFA intake were seen in the spine, total body, and Ward’s triangle BMD, suggesting that HT may influence PUFA associations with BMD. This study is registered with clinicaltrials.gov, identifier: NCT00000399.